The attitudes of healthcare professionals in Turkey toward the coronavirus vaccine - Azizoğlu, Fatma; Terzi, Banu; Topçu Tarakçı, Nesrin (Wiley, 2022)
Aim To identify healthcare professionals' attitudes toward the coronavirus vaccine. Background Controlling the coronavirus pandemic depends on achieving a high level of herd immunity. Accordingly, it is very important that healthcare professionals become role models by displaying positive attitudes toward vaccination. Methods This cross-sectional study was conducted between March and April 2021 with a total of 309 healthcare professionals. Data were collected via an online surveys using an "Introductory Information Form" and "Attitudes Towards the COVID-19 Vaccine Scale." One-way variance analysis and Bonferroni correction were used for the comparison of nonnormally distributed quantitative variables between more than two groups. The Kruskal-Wallis test and Dunn-Bonferroni test were used to compare non-normally distributed quantitative variables between more than two groups. Pearson correlation analysis was performed to evaluate the relationships between the quantitative variables. Results Regarding the healthcare professionals' attitudes towards the COVID-19 vaccine, the average score of positive attitudes was 3.52 +/- 0.87, and the average score of negative attitudes was 3.39 +/- 0.68. A statistically significant weak relationship was found between the ages of the participants and the average score of their positive attitudes towards the COVID-19 vaccine. The negative attitude score of the individuals who wanted to get the coronavirus vaccine was significantly higher than those who were undecided or did not want to get the vaccine. Conclusions Healthcare professionals completely agreed with the opinion "I would persuade everyone around me to get the coronavirus vaccine," and completely disagreed with the opinion "I believe that they will inject microchips to people with the coronavirus vaccine." Healthcare professionals have positive attitudes toward the COVID-19 vaccine. COVID-19-vaccinated participants' positive and negative attitude scores were found higher than those who were not vaccinated. Implications for nursing and health policy Supportive social activities should be organized in the public sense so that healthcare professionals act as a role model by displaying positive attitudes toward vaccination.
Keywords: Attitudes; COVID-19; Healthcare Professionals; Pandemic; Vaccine